Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 63647 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Platichthys flesus (Linnaeus, 1758)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 63647 records from 104 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004450-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences